(untitled) (Research, Society and Development, 2022)
Obesity is an increasingly common disease, whose prevalence has already reached epidemic proportions and is strongly associated with an increased risk of outcomes, whether cardiovascular, cancer or mortality. The objective of this review is to approach the main pathologies related to obesity, as well as to discuss possible strategies to reduce the damage to the health of these individuals. This is a narrative review study, carried out between October and November 2021, with a descriptive approach, in the Scientific Electronic Library Online (SciELO) and Latin American and Caribbean Center on Information in Science Sciences. Health (Bireme). The articles were selected based on the following keywords in Portuguese: “obesity” AND “metabolic syndrome”, “obesity” AND “type II diabetes”, “obesity” AND “cardiovascular diseases” and “obesity” AND “obstructive apnea of sleep”. Inclusion criteria were full articles published between January 2015 and July 2021 identified in October 2021. In total, 10 articles comprised this review. A relationship was found between obesity and the development or aggravation of Metabolic Syndrome, Obstructive Sleep Apnea, Type II Diabetes Mellitus and cardiovascular diseases. It is concluded that obesity is considered a public health problem considering that the emergence of new diseases can be caused by overweight, causing harm to metabolic and cardiovascular aspects. We emphasize the need for health professionals to seek knowledge about these pathologies, as well as guidelines for this population, so that interventions are carried out effectively and safely, ensuring better health outcomes.